Inheritance and Innovation of Mongolian Dance Creation from the Perspective of Cultural Anthropology - Xing, Yupeng; Potiwetchakul, Assoc. Prof. Dr. Supavadee; Fan, Assoc. prof. Dr. Di (Journal of Dhamma for Life, 2023)
This paper analyzes the reasons for inheritance and innovation in the process of Mongolian dance creation from the perspective of cultural anthropology. Interview choreographers in Inner Mongolia who directly participated in the choreography and won the "Chinese Dance Lotus Award" as the research object. From the perspective of cultural anthropology, this paper discusses the creative factors of inheritance and innovation in the creation of Mongolian dance, and the relationship between dance as a cultural symbol and globalization and modernity. The Mongols are a people who sing and dance on the grassland. Mongolian dance has been passed down as its unique culture. According to records, Mongolian dance has a history of nearly one thousand years. Its folk dance mainly includes top bowl dance, chopstick dance, Andai dance, Chama dance four forms, with a strong national flavor, is a rare artistic treasure in the world national culture inheritance. With the rapid development of modern society, the inheritance of Mongolian dance has suffered a certain impact. On this basis, the analysis and discussion on the inheritance status of Mongolian dance creation and arrangement is helpful to put forward constructive suggestions for its future development.